Bridging the Gap in Lifelong Learning: Policy, Technology, and Access - Rahman, Najib Aulia; Rizqi, Putri Umrotur (Yayasan Sinergi Kawula Muda, 2024)
Lifelong learning is increasingly recognized as a cornerstone of equitable and sustainable education systems in the digital age. This narrative review explores the global trends, challenges, and policy implications of lifelong learning, with a focus on digital inclusion, adult education, and equitable access. Drawing on a systematic review of academic literature from databases such as Scopus and Google Scholar, the study synthesizes findings related to the role of digital technologies, inclusive strategies, and policy frameworks. The analysis reveals that while digital tools such as online learning platforms and AI-enabled systems offer significant potential to expand access and personalize learning, several systemic barriers persist. These include infrastructural deficits, low digital literacy, economic disparities, and cultural stigma toward adult education. Furthermore, while many policies support lifelong learning, their impact is often limited by lack of alignment with learners' socio-cultural realities. The discussion highlights the interplay of policy, economy, and culture in shaping lifelong learning outcomes and proposes several solutions, including inclusive policy design, cross-sector collaboration, and community-based education. The review concludes that lifelong learning must be reimagined through inclusive, flexible, and context-sensitive frameworks. Future research should address the limitations in empirical evidence on long-term outcomes and explore hybrid models tailored to resource-constrained settings. Such efforts are essential for building adaptive and inclusive education systems that empower individuals and promote social equity.